Nursing Role In The Implementation Of Emergency Patients With Interruption Of The Cardiovascular Systemat The Review Of Nurse Knowledge In Aisyiyah Hospital Ponorogo - Gunarto, Gunarto; Setiyani, Dwi; Iswahyudi, Prima; Hildania, Hildania (Journal Of Nursing Practice, 2018)
Background: Knowledge or cognitive is a very important domain in shaping ones actions or overt behavior. Purpose : The purpose of this study is to analyze the relationship of knowledge and role of nurses in the handling of emergency patients in Aisyiyah Ponorogo General Hospital Methods : The design of correlative quantitative research with cross sectional research approach. This study uses independent variables. Knowledge of the nurse is the result of know to improve the behavior of nurse as executor in handling of emergency of cardiovascular system disorder and dependent variable of nurse role that is nurse behavior in handling of emergency of cardiovascular system disorder. The population is all nurses of IGD and ICU / ICCU in RSU Aisyiyah Ponorogo with sample of 25 respondents in Purposive Sampling. Data were collected using questionnaire and observation sheet then analyzed by Spearman Rank Correlation test. Result : The results of research almost half (36%) as many as 9 respondents have good knowledge. Spearmank Rank Correlation sig. (2-tailed) with 0.05> 0.007). Conclusion : The nurses knowledge is greatly influenced by the level of education of a person, and is linked, either directly or indirectly to the role of nurses in the treatment of emergency in patients with cardiovascular system disorders